Translating community-based participatory research into broadscale sociopolitical change: insights from a coalition of women firefighters, scientists, and environmental health advocates - Jennifer Liss Ohayon; Sharima Rasanayagam; Ruthann A Rudel; Sharyle Patton; Heather Buren; Tony Stefani; Jessica Trowbridge; Cassidy Clarity; Julia Green Brody; Rachel Morello-Frosch (BMC, 2023)
Abstract Background We report on community-based participatory research (CBPR) initiated by women firefighters in order to share successful elements that can be instructive for other community-engaged research. This CBPR initiative, known as the Women Worker Biomonitoring Collaborative (WWBC) is the first we are aware of to investigate links between occupational exposures and health outcomes, including breast cancer, for a cohort of exclusively women firefighters. Methods In order to be reflective of the experiences and knowledge of those most intimately involved, this article is co-authored by leaders of the research initiative. We collected leaders' input via recorded meeting sessions, emails, and a shared online document. We also conducted interviews (N = 10) with key research participants and community leaders to include additional perspectives. Results Factors contributing to the initiative's success in enacting broadscale social change and advancing scientific knowledge include (1) forming a diverse coalition of impacted community leaders, labor unions, scientists, and advocacy organizations, (2) focusing on impacts at multiple scales of action and nurturing different, yet mutually supportive, goals among partners, (3) adopting innovative communication strategies for study participants, research partners, and the broader community, (4) cultivating a prevention-based ethos in the scientific research, including taking early action to reduce community exposures based on existing evidence of harm, and (5) emphasizing co-learning through all the study stages. Furthermore, we discuss external factors that contribute to success, including funding programs that elevate scientist-community-advocacy partnerships and allow flexibility to respond to emerging science-policy opportunities, as well as institutional structures responsive to worker concerns. Conclusions While WWBC shares characteristics with other successful CBPR partnerships, it also advances approaches that increase the ability for CBPR to translate into change at multiple levels. This includes incorporating partners with particular skills and resources beyond the traditional researcher-community partnerships that are the focus of much CBPR practice and scholarly attention, and designing studies so they support community action in the initial stages of research. Moreover, we emphasize external structural factors that can be critical for CBPR success. This demonstrates the importance of critically examining and advocating for institutional factors that better support this research.